The Power of Nyai in The Development of The Pesantren - Adnani, Kamila; Mahbub, Moh. (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This reserach aims to explore the power of Nyai in the Pesantren Kholifatullah Singo Ludiro, Mojolaban, Sukoharjo, from the perspective of gender equality. The pesantren is under the leadership of Nyai Lilis Patimah, after the death of his husband KH Agung Syuhada’. This research is based on empirical data collected through such techniques as observation, interviews, and documentation. The result of the research shows that the active role of Nyai Lilis Patimah in the development of the pesantren indicates that kyai and nyai play equally essential roles in the development process. Indeed, Nyai Lilis Patimah owes her power to the symbolic or cultural, economic, and social capitals she has acumulated since the era of KH Agung Syuhada’s leadership. After his death, it is Nyai Lilis Patimah who dictates the policy on and determine the direction of the development of the pesantren to the extent that it achieves unprecendented success. Hopefully, by showing the power of nyai in the Pesantren Kholifatullah Singo Ludiro, this research can contribute to removing the social stigma to the leardership of women in the public arena.